The Role Of Compensation In Medical Dispute Resolution : Legal And Ethical Implications - Helmawan Trintono Subekti; Dahlan Dahlan; Tamaulina Br. Sembiring; Yasmirah Mandasari Saragih (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Compensation in the resolution of medical disputes in Indonesia is crucial as it provides financial compensation for patients who have suffered losses due to malpractice. Data shows an increase in the number of complaints and lawsuits related to medical disputes each year. Determining fair and proportional compensation often poses complex challenges as it involves various aspects such as the level of patient loss, healthcare service standards, medical evidence, and socio-economic factors. Therefore, a careful and holistic approach is needed in determining compensation to ensure justice and improve healthcare practices. The aim of this study is to identify the role of compensation in the resolution of medical disputes in Indonesia and to analyze its legal and ethical implications. The research method used is qualitative with a normative juridical and empirical approach. The results show that compensation in the resolution of medical disputes in Indonesia is important to ensure justice for patients and the responsibility of healthcare providers. The process of determining compensation involves mediation, negotiation, and formal legal processes. The Health Law and health regulations require hospitals to have dispute resolution mechanisms and provide patients with legal rights to compensation. Legal and ethical aspects such as integrity and justice are considered in determining compensation, creating a holistic dispute resolution system to maintain justice and the quality of healthcare services.